2010
DOI: 10.1007/s10529-010-0258-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes of grass carp Ctenopharyngodon idellus for the normalization of quantitative real-time PCR

Abstract: Expression of four reference genes of grass carp, including beta-actin (ACTB), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), 18S rRNA (18S) and elongation factor-1 alpha (EF1alpha), was studied in tissues of normal individuals and bacteria-infected individuals. EF1alpha had the most stable expressions followed by 18S rRNA then GAPDH; ACTB had the least stability. After being infected with bacteria, the grass carp showed minimal changes in expression levels of EF1alpha in the liver and head kidney, while AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The expression of g-type gene has been shown to be enhanced in carp after bacterial infection [19] and in the head kidney of brill after LPS treatment [20]. In this study, both the normalized and unnormalized data demonstrated that the expression of g-type gene in the guts and gut-free bodies of B. japonicum is increased following challenge with LPS or LTA.…”
Section: Discussionmentioning
confidence: 52%
“…The expression of g-type gene has been shown to be enhanced in carp after bacterial infection [19] and in the head kidney of brill after LPS treatment [20]. In this study, both the normalized and unnormalized data demonstrated that the expression of g-type gene in the guts and gut-free bodies of B. japonicum is increased following challenge with LPS or LTA.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, transcription of the ribosomal subunit may be affected by biological factors and by certain drugs (Spanakis 1993). Moreover, the quantity of rRNA present in cells constitutes 85-90% of the total RNA, and the regulation of rRNA synthesis is independent of mRNA (Ye et al 2010). Due to the high abundance of rRNA transcripts, when using rRNA genes as references for quantification of genes with relatively low expression levels, the cDNA templates may need to be diluted to improve comparison, increasing the chance of experimental error (Nicot et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…18S rRNA was used as internal control in order to standardize the results by eliminating variations in mRNA and cDNA quantity and quality. We firstly tested the stability of 18S rRNA during development and gonadal developmental stages based on the reports of Ye et al (2010). The expression of 18S rRNA showed stable values during our assay.…”
Section: Real-time Quantitative Rt-pcr Analysismentioning
confidence: 99%